REPRODUCTION AND PRODUCTION PERFORMANCE OF PIG ON LOCAL FARM AT TWO DIFFERENT LOCATIONS - SURANJAYA I G.; M. DEWANTARI; I K. W. PARIMARTHA; I W. SUKANATA; I N. T. ARIANA (Majalah Ilmiah Peternakan, 2018)
The research was conducted in a survey of farmers on the pig farm business in the Kebek and Penginyahanvillage, Payangan-Gianyar. Purposive random sampling of 20 farmers in each location and explorative approachwas conducted to describe the production and reproduction management applied. Data were analyzed descriptivelyand to study production and reproduction management between the two sites was Two Independent Sample TTest. The results showed the average productivity of pigs in Kebek and Penginyahan that is litter size: 9,50±1,65 vs10,86±1,68 tail, annual litter size : 2,10±0,32 vs 2,29±0,49 times, weaning age: 29,00±2,11 vs 29,00±1,91 day, andthe three variables were not significantly different (P>0,05). The average number of piglet weaned in Kebek andPenginyahan was 7.90±1,45 vs 9,43±1,99 head, weaning weight of piglet 7,20±1,69 vs 5,29±0.57 kg (P <0.05). Thedry period and the age of culled of sow in Kebek is significantly higher than in Penginyahan (P<0.05). Whereas infattening management, early age to fatten and length of maintenance is not different between the two locations(P>0,05), whereas the live and slaughtering weight in Kebek are significantly higher than those in Penginyahan thatis 14.00±1,15 vs. 12.20±1,79 kg and 126,50±11,80 vs. 114±10,84 kg (P<0,05).